+0  
 
0
25
1
avatar

Simplify sqrt(2)*sqrt(6)*sqrt(110)*sqrt(156).

 Jul 23, 2022
 #1
avatar+124524 
+1

sqrt (2) * sqrt (6) * sqrt (110) * sqrt (156)   =

 

sqrt (2)  * [ sqrt (2) * sqrt (3) ] * [ sqrt (11) * sqrt (5) * sqrt (2) ] * [sqrt (4) * sqrt (3) * sqrt (13) ] =

 

sqrt (2) * sqrt (2) * sqrt (2) * sqrt (4)  *  sqrt (3) * sqrt (3) * sqrt (11) * sqrt (13) * sqrt (5)  =

 

2 * sqrt (2) * 2 * 3 * sqrt (11) * sqrt (13) * sqrt (5)  =

 

12 *  sqrt  [ 2 * 11 * 13 * 5 ] =

 

12 sqrt [ 1430 ]

 

 

cool cool cool

 Jul 23, 2022

12 Online Users